Finite element and experimental analysis of the micro-form rolling process - Cregan, Emmet (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2007)
The observations made during this research which, to the best knowledge of the author have not been previously mentioned in literature, were as follows: -- Loss of contact between the die and workpiece when rolling small diameter parts and the subsequent deviation of the workpiece groove geometry from the die geometry was predicted using FEA and observed experimentally. -- Literature predicted a laminar strain pattern in the workpiece in which the maximum values were located at the workpiece surface. The laminar pattern was confirmed during this research and, using 3D FEA, it was for the first time attributed to the rotational nature of the form rolling process. -- Die designs that prevented the formation of axial and helical laps on form rolled parts were designed and tested. -- The novel 'one-die rolling' process was trialled and proved to be a viable process.
Keywords: Mechanical Engineering, Ph.D.; Ph.D. Trinity College Dublin